1999
DOI: 10.1002/1529-0131(199902)42:2<229::aid-anr4>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of B7 costimulatory molecules by salivary gland epithelial cells in patients with Sj�gren's syndrome

Abstract: Objective. To investigate the expression of B7 costimulatory molecules in the lymphoepithelial lesions of salivary gland (SG) biopsy tissues and in SG epithe-lial cell lines derived from patients with Sjögren's syndrome (SS). Methods. B7.1 and B7.2 protein expression was studied by immunohistochemistry in minor SGs obtained from 11 patients with SS and 10 disease control patients with nonspecific sialadenitis and in cultured SG epithelial cell lines obtained from minor SGs from 15 SS patients and 15 control pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
10

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 56 publications
5
80
0
10
Order By: Relevance
“…All cultures were incubated at 37°C, 5% CO 2 , and 99% humidity. The epithelial origin of SGEC lines was routinely verified immunocytochemically by the expression of epithelialspecific cell markers such as cytokeratins, as previously described (31). SGEC cultures were free of T and B cells, macrophages, and dendritic cells, as indicated by the absent expression of such cell type-specific markers (data not shown).…”
Section: Salivary Gland Epithelial Cellsmentioning
confidence: 72%
See 3 more Smart Citations
“…All cultures were incubated at 37°C, 5% CO 2 , and 99% humidity. The epithelial origin of SGEC lines was routinely verified immunocytochemically by the expression of epithelialspecific cell markers such as cytokeratins, as previously described (31). SGEC cultures were free of T and B cells, macrophages, and dendritic cells, as indicated by the absent expression of such cell type-specific markers (data not shown).…”
Section: Salivary Gland Epithelial Cellsmentioning
confidence: 72%
“…SS was diagnosed on the basis of the European SS classification criteria (32). Nonneoplastic long-term SGEC cultures were developed, characterized, and maintained, as previously described (31). Briefly, primary cultures were established by explant outgrowth technique in a medium consisting of a 3:1 mixture Ham's F12 and DMEM (Life Technologies) supplemented with 2.5% FBS (Life Technologies), 0.4 g/ml hydrocortisone (Upjohn, Kalamazoo, MI), 0.125 U/ml insulin (Novo, Bagsvaerd, Denmark), 10 ng/ml epidermal growth factor (Promega, Madison, WI), 2 mM glutamine, 100 U/ml penicillin, and 100 g/ml streptomycin.…”
Section: Salivary Gland Epithelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigators have suggested that polarized Th1 balance is associated with the pathogenesis of SS (35)(36)(37). IFN␥ induces expression of HLA-DR and costimulatory molecules such as CD40 and B7 on salivary epithelial cells, resulting in the promotion of autoimmune reactions between epithelial cells and lymphocytes (38)(39)(40). In addition, the Th1-associated chemokines IP-10, Mig, and I-TAC have been reported to be predominantly expressed in the ductal epithelium, leading to the accumulation of T cell infiltrates in the salivary glands of patients with SS (8,9).…”
Section: Discussionmentioning
confidence: 99%